MECHANISMS OF CREATING A PROFESSIONAL INFORMATION ENVIRONMENT IN PREPARING FUTURE LOGICAL THERAPISTS TO WORK WITH CHILDREN WITH SEVERE SPEECH DISORDERS - Achilova Sevara Djasirkulovna (Modern American Journals, 2025)
In this article, the author presents information about the mechanisms for creating a professional information environment when training future speech therapists to work with children with severe speech disorders. The methods of working with children with severe speech disorders, the necessary knowledge and skills, as well as ways to create an information environment are outlined.
Keywords: Defectology, correctional pedagogy, inclusive education, differentiation, technology, educational paradigm, speech defect dysarthria, speech defect rhinolalia, speech defect stuttering, articulatory speech apparatus, phonemic perception.